(untitled) (Stavební obzor - Civil Engineering Journal, 2021)
Coupling beam damper can be easily repaired in the post-earthquake, which can dissipate the seismic energy of the structure in the earthquake action. In this paper, the seismic mitigation efficiency of the coupling beam damper in the shear wall structure is analysed by using the fast nonlinear analysis method. Meanwhile, the effect of the layout location and number of the coupling beam dampers on the seismic mitigation efficiency of the structure are studied. Finally, the effect of the performance parameter of the coupling beam damper on the seismic mitigation efficiency is also analysed. The results indicate that: the story shear force and the drift angle of the shear wall structure can be effectively decreased because of the coupling beam damper, and the maximum decreased amplification of the story drift angle and base shear force can reach up to 16.7% and 8.8% respectively. Relating to the decreased amplification of the base shear force, the decreased amplification of the story drift angle of the structure with coupling beam damper is obvious. The coupling beam damper installed in the upper part of the structure is more economical, because the deformation of the structural coupling beam is mainly concentrated in the upper part of the structure. To ensure economic of the structure with damper, the reasonable coupling damper performance parameter should be determinate according to the dynamic response of the shear wall structure in the earthquake action. The above research work can provide guidance for the seismic design of the shear wall structure.